A review of Pliomegatherium Kraglievich, 1930 (Xenarthra: Phyllophaga: Megatheriidae) - Brandoni, Diego (2006)
Eight species of Megatheriinae have been recognized from the "Conglomerado osífero" of the Ituzaingó Formation (Upper Miocene-Pliocene) of Argentina, but the validity of some of these taxa is doubtful. The taxonomic status of one of them, Pliomegatherium, is assessed based on restudy of the original material on which the species were originally based. The morphological differences observed in the type specimens of Pliomegatherium lelongi and Pliomegatherium paranensis do not justify the specific separation, being Pliomegatherium paranensis a junior synonym of Pliomegatherium lelongi.